Pelatihan Pemanfaatan Limbah Sekam Padi pada Siswa SMA Eunterpreneurship Chevalier Anasai Merauke - Henie Poerwandar Asmaningrum; Martha Betaubun; Alexander Phuk Tjilen (LPPM Universitas Bumigora, 2022)
The absence of assistance and training efforts to the community regarding rice husk waste management is the focus of this PDM program. In this program, students will assist the community in processing rice husk waste into various products that can be used alone or sold again so as to improve the community's economy. The target of this activity is ECA High School students, the majority of whom are indigenous Papuans. Rice husk waste is processed into briquettes and planting media that can be used alone or sold again to improve the lives of students and the community. This program is able to increase the knowledge and ability of the community in processing rice husk waste, which has an impact on improving public health and education as well. In addition, this program will provide new knowledge insights for students, as well as trigger students' critical attitude and creativity in solving problems in the surrounding community.